Opioid initiation and injection transition in rural northern New England: A mixed-methods approach. (1st December 2020) - Nolte, Kerry; Drew, Aurora L.; Friedmann, Peter D.; Romo, Eric; Kinney, Linda M.; Stopka, Thomas J.
Highlights: The majority of injection initiation occurred younger than 25 years of age. Normalization of drug use within the family and in the rural communities of study is extensive. Transitions to opioids and injection of drugs are described in tandem with traumatic events. Enhanced trauma-informed care in integrated substance use and mental health services is recommended. Abstract: Background: In rural northern New England, located in the northeastern United States, the overdose epidemic has accelerated with the introduction of fentanyl. Opioid initiation and transition to opioid injection have been studied in urban settings. Little is known about opioid initiation and transition to injection drug use in rural northern New England. Methods: This mixed-methods study characterized opioid use and drug injection in 11 rural counties in Massachusetts, Vermont, and New Hampshire between 2018 and 2019. People who use drugs completed audio computer-assisted self-interview surveys on substance use and risk behaviors (n = 589) and shared personal narratives through in-depth interviews (n = 22). The objective of the current study is to describe initiation of opioid use and drug injection in rural northern New England. Results: Median age of first injection was 22 years (interquartile range 18–28 years). Key themes from in-depth interviews that led to initiating drug injection included normalization of drug use in families and communities, experiencing trauma, and abrupt discontinuation of an opioid prescription. Other factors that led to a transition to injecting included lower cost, increased effect/ rush, greater availability of heroin/ fentanyl, and faster relief of withdrawal symptoms with injection. Conclusions: Trauma, normalization of drug use, over-prescribing of opioids, and abrupt discontinuation challenge people who use drugs in rural northern New England communities. Inadequate opioid tapering may increase transition to non-prescribed drug use. The extent and severity of traumatic experiences described highlights the importance of enhancing trauma-informed care in rural areas.